Sleep propensity in psychiatric hypersomnolence: A systematic review and meta-analysis of multiple sleep latency test findings. (February 2017) - Plante, David T.
Summary: Hypersomnolence plays a sizeable role in the course and morbidity of psychiatric disorders. Current sleep medicine nosology is reliant on the multiple sleep latency test (MSLT) to segregate hypersomnolence associated with psychiatric disorders from other central nervous system causes. However, the evidence base regarding sleep propensity in psychiatric hypersomnolence as measured by the MSLT has not been systematically evaluated, which is vital to clarify the utility and validity of current nosological schema. In this review, the use of sleep propensity assessed by the MSLT in patients with psychiatric hypersomnolence is systematically evaluated, using both qualitative and quantitative assessment. Findings demonstrate high heterogeneity and potential for bias among studies, with a pooled estimate of sleep propensity among patients with psychiatric hypersomnolence similar to normative values. Additionally, approximately 25% of patients with psychiatric hypersomnolence demonstrate a mean sleep latency below 8 min, the current cutpoint to define pathologic sleepiness. These data underscore the limitations of the MSLT in segregating psychiatric hypersomnolence from other central nervous system hypersomnias. Further research is warranted to evaluate novel measures and biomarkers of excessive sleepiness to advance clinical practice, as well as dimensional approaches to classification of hypersomnolence disorders.